2003
DOI: 10.1037/0033-2909.129.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of posttraumatic stress disorder and symptoms in adults: A meta-analysis.

Abstract: A review of 2,647 studies of posttraumatic stress disorder (PTSD) yielded 476 potential candidates for a meta-analysis of predictors of PTSD or of its symptoms. From these, 68 studies met criteria for inclusion in a meta-analysis of 7 predictors: (a) prior trauma, (b) prior psychological adjustment, (c) family history of psychopathology, (d) perceived life threat during the trauma, (e) posttrauma social support, (f) peritraumatic emotional responses, and (g) peritraumatic dissociation. All yielded significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

194
2,057
23
62

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,046 publications
(2,336 citation statements)
references
References 145 publications
194
2,057
23
62
Order By: Relevance
“…Our finding that conditional PTSD risk is elevated after traumas involving violence is broadly consistent with previous research (see reviews in Atwoli et al, 2015; Ozer, Best, Lipsey, & Weiss, 2003). We also found that prior exposure to some traumas involving violence was associated with generalized vulnerability to subsequent PTSD.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that conditional PTSD risk is elevated after traumas involving violence is broadly consistent with previous research (see reviews in Atwoli et al, 2015; Ozer, Best, Lipsey, & Weiss, 2003). We also found that prior exposure to some traumas involving violence was associated with generalized vulnerability to subsequent PTSD.…”
Section: Discussionsupporting
confidence: 91%
“…Among the well-known risk factors or covariates of posttraumatic stress are high severity of exposure (Santiago et al, 2013), being female (Olff, Langeland, Draijer, & Gersons, 2007), low levels of social support (Charuvastra & Cloitre, 2008; Ozer, Best, Lipsey, & Weiss, 2003), and high neuroticism (Ormel et al, 2013). Despite the numerous studies that have investigated these factors as predictors of posttraumatic stress, few have examined why or how they lead to the development of posttraumatic stress symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…Variables modifying the risk of developing posttraumatic stress can be classified as pretrauma, peritrauma or posttrauma variables (Schnurr, Lunney, & Sengupta, 2004). In meta-analyses, peritrauma and posttrauma variables had a higher predictive value of posttraumatic stress than pretrauma variables (Brewin et al, 2000; Ozer, Best, Lipsey, & Weiss, 2003; Trickey, Siddaway, Meiser-Stedman, Serpell, & Field, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Among the peritrauma variables found to be predictive of posttraumatic stress are perceived life threat during the trauma, peritraumatic emotional responses and peritraumatic dissociation (Ozer et al, 2003). Although peritraumatic dissociation attained the highest effect size ( r  = .35) in the meta-analysis performed by Ozer et al (2003), more recent findings question whether peritraumatic dissociation can be considered an independent predictor (Hagenaars, van Minnen, & Hoogduin, 2007; van der Velden & Wittmann, 2008).…”
Section: Introductionmentioning
confidence: 99%